ACUTE RESPIRATORY TRACT INFECTIONS: WIDENING OF POSSIBILITIES OF ANTIVIRAL TREATMENT - V. A. Bulgakova (Вопросы современной педиатрии, 2013)
Problem of effective and safe treatment and prophylaxis of acute respiratory tract infections is one of the most topical problems in clinical pediatrics. In this article the possibility of usage in treatment of acute respiratory viral infections an immunostimulating drug with antiviral action — pranobex. The author describes mechanisms of combined immunomodulatory and antiviral action of this drug, shows data on its efficacy and tolerability in children. The demonstrated data of literature review and the results of the author’s own studies evidenced that administration of inosine pranobex relieved symptoms of acute respiratory viral infection, prevent development of complications and restores the weakened immunity, allows decreasing of the requirements of other drugs and medicinal load to the organism. Characteristics of this drug widen the possibilities of pharmacotherapy of acute respiratory viral infections in children. Anaysis of publications on efficacy of this drug, as well as the author’s own data allow to recommend inosine pranobex for treatment of acute respiratory tract infections in frequently ill children, patients with chronic diseases (including allergic disorders of the respiratory tract) and intercurrent acute respiratory tract infections.